The effect of Facebook use on academic job performance / Nina Farisha Isa... [et al.] - Isa, Nina Farisha; Abdullah, Hasniza; Razali, Mohamad Azli; Mohd Said, Noraslinda; Ngelambong, Anderson (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
As an academic use of social networking sites (SNS) has been playing a vital role in the way of doing business in education industry. Therefore, the present study is to propose a concept of ‘task characteristics’ using task- technology fit model. In this regard, this paper extend knowledge from Lee and Lee (2018) model that examine the use of Facebook on office workers. However, there is still lack of study about the relationship between SNS use and job performance in the context of academic industry especially in hospitality and tourism faculty. Thus, this study has implications for academic industry that are concerned about formulating policies related to academic use of SNS.